To know about science is to love it? Unraveling cause–effect relationships between knowledge and attitudes toward science in citizen science on urban wildlife ecology. Issue 8 (4th May 2021) - Bruckermann, Till; Greving, Hannah; Schumann, Anke; Stillfried, Milena; Börner, Konstantin; Kimmig, Sophia E.; Hagen, Robert; Brandt, Miriam; Harms, Ute
Abstract: Nowadays, citizens collaborate increasingly with scientists in citizen science (CS) projects on environmental issues. CS projects often have educational goals and aim to increase citizens' knowledge with the ultimate goal of fostering positive attitudes toward science. To date, little is known about the extent to which CS projects strengthen the positive interrelationship between knowledge and attitudes. Based on previous research, it has been suggested that the knowledge–attitude relationship could be further examined by focusing on different aspects: (1) different attitudinal domains, (2) topic‐specific knowledge, and (3) its direction. Our study contributes to the clarification of the interrelation between scientific knowledge and attitudes toward science within the specific domain of urban wildlife ecology using cross‐lagged panel analyses. We collected survey data on five attitudinal domains, topic‐specific knowledge, scientific reasoning abilities, and epistemological beliefs from N = 303 participants before and after they participated in a CS project on urban wildlife ecology. Participants collected and analyzed data on terrestrial mammals in a German metropolitan city. Our results provide evidence for the relationship between knowledge and attitudes due to the topic‐specificity of knowledge in CS projects (e.g., wildlife ecology). Our method provided a rigorous assessment of the direction of the knowledge–attitude relationship and showed that topic‐specific knowledge was a predictor of more positive attitudes toward science.